The 1st Virtual Conference on Social Science in Law, Political Issue and Economic Development - Andista Candra Yusro; Mochammad Tanzil Multazam; Robbi Rahim (Sciendo, 2021)
We are delighted to introduce the Virtual Conference on Social Science In Law, Political Issue And Economic Development 2020 with theme “Realizing Society 5.0 for a Better Life”. The technical program has brought researchers and practitioners around the world to a good forum for discussing, leveraging and developing all scientific and technological aspects that are relevant to economic business, education and humanities. Moreover, it is a great pleasure to have the keynote and invited speakers of VCOSPILED 2020, Prof. Dr. Pujiono, Assoc. Prof. Ilham Sentosa, Ph.D and Dr. Siska Diana Sari, S.H., M.H who will share their knowledge and best innovative research findings in economic business, education and humanities. This conference is held by Kresna Acitya Media Nusantara in collaboration with Universitas Muhamadiyah Sidoarjo and Relawan Jurnal Indonesia. Kresna Acitya Media Nusantara is a company that is dedicated to maximize the impact of scientific publication, and Relawan Jurnal Indonesia, is a non-profit organization in the field of scientific publication. The conference will be held virtually using Zoom webinar on October 15, 2020. This conference has successfully acquired 180 participants and 55 presenters from 4 countries, Indonesia, Malaysia, Taiwan and Uzbekistan. Thus, all selected papers will be submitted for publication to our publishing partner SCIENDO. We hope that the future VCOSPILED 2020 will be as successful and stimulating, as indicated with the contributions presented in this volume. Aims and Scope The VCOSPILED is an academic conference that centered in Social Science In Law, Political Issue And Economic Development, is open and welcoming to contributions from the many disciplines and approaches that meet at the crossroads that is communication study. We are interested in scholarship that crosses disciplinary lines and speaks to readers from a range of theoretical and methodological perspectives. In other words, the VCOSPILED will be a forum for scholars when they address the wider audiences of our many sub-fields and specialties, rather than the location for the narrower conversations more appropriately conducted within more specialized conferences. We suggest the following broad areas of research: Economics & Business Education Humanities Interdisciplinary Studies Policy, Politics, and Communication Editorial Policy VCOSPILED Guidelines for Reviewers VCOSPILED Instruction for Authors VCOSPILED ABSTRACTING & INDEXING Conference is covered by the following services:Baidu ScholarBayerische StaatsbibliothekBDSBowker Book DataCiandoCNKI Scholar (China National Knowledge Infrastructure)DimensionsEBSCOExLibrisGoogle BooksGoogle ScholarNavigaReadCubeSemantic ScholarTDOne (TDNet)WorldCat (OCLC)X-MOLAdditionally, the proceedings volume is registered and indexed in the Crossref database.